Obesity-Related Inflammation and Endothelial Dysfunction in COVID-19: Impact on Disease Severity - De Lorenzo A; Estato V; Castro-; Tibirica E (Dove Medical Press, 2021)
Andrea De Lorenzo,1 Vanessa Estato,2 Hugo C Castro-Faria-Neto,2 Eduardo Tibirica1 1Instituto Nacional de Cardiologia, Rio de Janeiro, RJ, Brazil; 2Laboratorio de Imunofarmacologia, Instituto Oswaldo Cruz, FIOCRUZ, Rio de Janeiro, RJ, BrailCorrespondence: Andrea De LorenzoInstituto Nacional de Cardiologia, Rua das Laranjeiras 374, Rio de Janeiro, RJ, 22240 006, BrazilTel +55 21 30372288Email andlorenzo@cardiol.brAbstract: The coronavirus disease 2019 (COVID-19) pandemic has put into evidence another pandemic – obesity. Currently, several studies have documented the association between obesity and COVID-19 severity. The mechanisms underlying the increased risk of complications and mortality in obese patients with COVID-19 are of diverse nature. Inflammation plays a central role in obesity. Metabolic alterations seen in obese patients are related to an inflammatory response, and several studies report elevated levels of circulating inflammatory cytokines in obese patients. Also, deregulated expression of adipokines, such as leptin and resistin, increase the expression of vascular adhesion molecule 1 and intercellular adhesion molecule 1 that contribute to increased vascular leukocyte adhesiveness and additional oxidative stress. Additionally, it is now recognized that the chronic impairment of systemic vascular endothelial function in patients with cardiovascular and metabolic disorders, including obesity, when intensified by the detrimental effects of SARS-CoV-2 over the endothelium, may explain their worse outcomes in COVID-19. In fact, vascular endothelial dysfunction may contribute to a unfavorable response of the endothelium to the infection by SARS-CoV-2, whereas alterations in cardiac structure and function and the prothrombotic environment in obesity may also provide a link to the increased cardiovascular events in these patients.Keywords: obesity, inflammation, COVID-19, endothelial dysfunction, microcirculation